The dive sites of the Philippines - Jackson, Jack (New Holland Publishers, 1995)
This is a guidebook for divers, or future divers, which focuses on dive sites in the Philippines. These are divided into areas: Luzon, Mindoro, Palawan, and the Visayas. It rates each dive site, gives the means of access, condition, average and minimum depths, and has an abundance of colored photographs and maps. It has a chapter on marine environment, which discusses different kinds of reefs and common fishes found in Philippine waters, as well as a chapter on underwater photography. A classified index is provided.